2013
DOI: 10.1038/ejhg.2013.39
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a PKP2 gene deletion in a family with arrhythmogenic right ventricular cardiomyopathy

Abstract: Arrhythmogenic right ventricular cardiomyopathy (ARVC) is a primary heart muscle disease characterized by progressive myocardial loss, with fibro-fatty replacement, and high frequency of ventricular arrhythmias that can lead to sudden cardiac death. ARVC is a genetically determined disorder, usually caused by point mutations in components of the cardiac desmosome. Conventional mutation screening of ARVC genes fails to detect causative mutations in about 50% of index cases, suggesting a further genetic heteroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 41 publications
0
28
0
Order By: Relevance
“…Recent studies have shown that stop-coding in diseasecausing genes are more pathogenic than missense mutations, since the former are causing alteration of protein length and conformation, leading to haploinsufficiency due to protein instability [67][68][69][70]. Entire PKP2 exons or even whole gene deletions have been recently described in AC families with a frequency of approximately 2 % [71][72][73]. These data are further stressing the question whether haploinsufficiency is enough to determine the disease phenotype.…”
Section: Ac Genes/mutations and Diagnostic Implicationsmentioning
confidence: 73%
“…Recent studies have shown that stop-coding in diseasecausing genes are more pathogenic than missense mutations, since the former are causing alteration of protein length and conformation, leading to haploinsufficiency due to protein instability [67][68][69][70]. Entire PKP2 exons or even whole gene deletions have been recently described in AC families with a frequency of approximately 2 % [71][72][73]. These data are further stressing the question whether haploinsufficiency is enough to determine the disease phenotype.…”
Section: Ac Genes/mutations and Diagnostic Implicationsmentioning
confidence: 73%
“…Hence, the first study was published in 2011 [48], which identified three PKP2 exon deletions among 149 individuals affected by ARVC. After that, in the last 3 years [58], Mura et al [59] reported cases of CNV in this pathology. Consequently, we strongly recommend that genetic testing in ARVC includes CNV screening when conventional sequencing analysis does not identify any pathogenic genetic variants in ARVC associated genes.…”
Section: Plakophilin-2mentioning
confidence: 96%
“…Genetic series have reported that 30-40 % carry a pathogenic genetic variant in the PKP2 gene, followed by DSP (10-15 %) [55], DSG2 (3-8 %) [56], and DSC2 (1-5 %) [57]. Recently, other genetic alterations such as copy number variations (CNV) in PKP2 gene have been associated with the disease but they are very rare [58,59]. Therefore, after a comprehensive genetic analysis, nearly 40 % of clinically diagnosed cases remain without identified genetic cause.…”
Section: Desmosomal Genesmentioning
confidence: 97%
“…2013; Li Mura et al. 2013), but the overall prevalence of CNVs in cardiomyopathy‐associated genes remains incompletely characterized.…”
Section: Introductionmentioning
confidence: 99%